THE IMPACT OF OIL PRICE FLUCTUATIONS ON THE GENERAL BUDGET OF IRAQ - Dr. ABDULHAMEED ALSABBAGH; ABBAS FADHIL JABER (Scholar Express Journal, 2023)
Abd al-Hamid, Abd al-Muttalib, “The Economics of Public Finance,” 1st edition, United Arab Company for Marketing and Supplies, Cairo, 2010. Abd al-Rahman, Osama, “The One Resource and the Prevailing Spending Approach,” 1st edition, Beirut, Center for Arab Unity Studies, 1988. Abdel-Majid, Abdel-Fattah Abdel-Rahman, “The Economics of Public Finance,” 2nd edition, 1996. Abdel-Samie, Osama El-Sayed, The Problem of Unemployment in Arab and Islamic Societies, Causes, Effects, Solutions, University Thought House, Alexandria, first edition, 2007. Ali, Ahmed Abrihi, “International Financial Economics and Monetary Policy,” 1st edition, Hammurabi Center for Research and Strategic Studies, Baghdad, 2012. Allam, Ahmed Abdel-Samie, “Public Finance,” 1st Edition, Al-Wafaa Law Library, Alexandria, 2012. Al-Nuaimi, Asma Mansi Yassin, The Organization of Petroleum Exporting Countries (OPEC) in light of international economic changes with reference to Iraq, a master’s thesis submitted to the Council of the College of Administration and Economics, University of Baghdad, 2007. Al-Sammak, Muhammad Azhar Saeed, Oil Economy and Oil Policy, Foundations and Applications, University of Mosul, Iraq, 1987. Al-Tamimi, Abbas Fadel Rasan, The impact of fluctuations in crude oil prices on stock markets, a master's thesis submitted to the Council of the College of Administration and Economics, University of Karbala, 2011. Brent Oil: Brent crude is considered a light oil because of its specific weight of (38) degrees and the low sulfur content that reaches (0.037%). It is used as a source for global oil pricing for two-thirds of global oil production, especially in the European and African markets. An oil well called Brent is located between Norway and Britain in the North Sea, and its oil was of high quality and free of impurities. Elahiti, Ahmed Hussein, An Introduction to Oil Economics, The Ideal House for Printing and Publishing, Beirut, first edition, 2011. Elahiti, Ahmed Hussein, Oil Economics, Mosul University Press, 2000. Fattouh, Bassam, “The Dynamics of Global Demand and Its Repercussions on the Producing Countries in the Middle East”, The Oil Age, Emerging Challenges, Emirates Center for Strategic Studies and Research, 1st edition, 2011. Kazem, Hassan Latif, Iraqi oil and oil policy in Iraq and the region under the American occupation, a future vision, Iraq Center for Studies, Iraq, first edition 2007. Khalaf, Falih Hassan, "Public Finance", 1st edition, The World of Modern Books, Jordan, 2008. Nashed, Suzy Adly, "Public Finance", Al-Halabi human rights publications, Lebanon, 2003. Prince, Fouad Qassem, The New in the Iraqi Oil Issue, Al-Ghad Press, Iraq, Baghdad, 2012. Salama, Mamdouh, the factors behind the sharp decline in crude oil prices, research and discussions on the symposium of the repercussions of falling oil prices on exporting countries, the Arab Center for Research and Policy Studies, Doha, November 7, 2015. Set-off: deduction of part of the debt of higher value between two persons who are both creditors and debtors at the same time. Shendi, Adeeb, and Lafteh, Abbas, The Impact of Oil on Determining the Economic and Financial Situation, Al-Nahda Magazine, Volume Thirteen, Issue One, January, 2012. Taqa, Muhammad, and Al-Azzawi, Huda, “The Economics of Public Finance,” 1st Edition, Dar Al-Masirah for Publishing and Distribution, Amman, 2007. West Texas Crude: It is a measure used in North America, the largest oil market in the world. It is light oil, its specific weight is (39) degrees, and it contains (0.024%) of sulfur. Yunus, Mansour Milad, “Principles of Public Finance”, Technical Institution for Printing and Publishing, Egypt, 2004.
Keywords: Oil prices; public budget; Iraqi economy